Serum Aldosterone as Predictor of Progression of Coronary Heart Disease in Patients Without Signs of Heart Failure After Acute Myocardial Infarction - Resic, Nerma (Med Arch, 2018)
INTRODUCTION: In patients with acute myocardial infarction (AMI) early risk assessment of development of complications is of great importance. It is proven that aldosterone level has a major role in progression of cardiovascular pathology. AIM: Determination of influence of aldosterone plasma level in the progression of heart disease in patients without signs of heart failure after AMI. MATERIAL AND METHODS: Research included 207 patients, hospitalized in the acute phase of myocardial infarction, and who were divided into two groups: 127 patients with no clinical signs of heart failure and 60 patients with heart failure. RESULTS: The serum aldosterone concentration was 73.4% higher in the group of decompensated patients, 128 pg/mL (75.4-236 pg/mL) in decompensated and 73.7 pg/mL (42.7 -115.25 pg/mL) in compensated. In the group of compensated patients, changes in aldosterone levels showed a statistically significant effect on the incidence of post-infarction angina (p=0.0001) as well as reinfarction (p=0.009). There is a connection between changes in aldosterone plasma level and positive stress test (p=0.012). CONCLUSION: In patients with AMI, elevated serum aldosterone level can be prognostic factor of the progression of coronary heart disease, development of heart failure, as well of development of post-infarction angina, myocardial reinfarction and pathological finding on the stress test.